Synthesis of copper oxide nanoparticles on activated carbon for pollutant removal in tartrazine structure - Jafari Rad, Azadeh (Journal of Composites and Compounds, 2020)
In this study, activated carbon particles were modified by copper oxide to remove the anionic Tartrazine dye from aqueous solutions. Adsorption studies were performed as batch studies and the influences of pH, initial dye concentrations, and contact times were evaluated. Maximum removal percentage was obtained for the initial concentration of 30 mg/L and the equilibrium of the adsorption was achieved within 60 minutes of contact time. The Langmuir and Freundlich kinetic models were used for analyzing the equilibrium data. It was shown that better fitting was observed by the Langmuir model. Pseudo-first-order and Pseudo-second-order kinetic models were also applied to understand the kinetics of the adsorption processes. It was found that the Tartrazine adsorption followed the pseudo-second-order kinetic model.